ANALISIS KUALITAS WEBSITE CORONA.JAMBIPROV.GO.ID MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - sintia amalia; Setiawan Assegaff; Xaverius Sika (LPPM STIKOM Dinamika Bangsa, 2021)
Abstract The corona.jambiprov.go.id website is a portal that provides news about Covid 19 in the province of Jambi which was built at the end of March 2020. From the observations made, several problems were found on the corona.jambiprov.go.id website, namely not providing all web sites of all districts that provide information related to the corona virus. The purpose of this study is to determine the level of quality and user ratings of the corona.jambiprov.go.id website based on the results of the analysis using webqual 4.0 and Importance Performance Analysis (IPA). Webqual is divided into 2 variables, namely the independent variable and the dependent variable. The independent variables consist of usability, information quality, service interaction quality. The dependent variable is user satisfaction. Data processing using SPSS IMB 25 software. Based on the results of questionnaire data processing distributed to the special community of Jambi province, it was found that in performance there were variables of service interaction quality that had more influence on the quality of the website and on expectations that the variable of service interactions quality also had more influence on the quality of the Corona.jambiprov.go.id.website. Keywords: Usability, Information Quality, Service Interaction Quality, User Satisfaction, Webqual Abstrak Website corona.jambiprov.go.id merupakan portal yang menyajikan berita seputar covid 19 diwilayah provinsi jambi yang dibangun pada akhir maret 2020. Dari pengamatan yang dilakukan, ditemukan beberapa masalah dalam website corona.jambiprov.go.id yaitu tidak menyediakan semua web dari semua kabupaten yang memberikan informasi terkait corona virus. Tujuan dari penelitian ini yaitu untuk mengetahui tingkat kualitas dan penilaian pengguna terhadap website corona.jambiprov.go.id berdasarkan hasil analisis menggunakan webqual 4.0 dan Importance Performance Analysis (IPA). Webqual terbagi menjadi 2 variabel yaitu variabel bebas dan variabel terikat. Variabel bebas terdiri dari kegunaan, kualitas informasi, kualitas interaksi layanan. Variabel terikat berupa kepuasan pengguna. Pengolahan data menggunakan software SPSS IMB 25. Berdasarkan hasil pengolahan data kuesioner yang disebarkan kepada masyarakat khusus provinsi Jambi didapatkan bahwa pada kinerja terdapat variabel kualitas interaksi layanan lebih berpengaruh terhadap kualitas website dan pada harapan variabel kualitas interaksi layanan juga lebih berpengaruh terhadap kualitas Website corona.jambiprov.go.id. Kata Kunci: Kegunaan, Kualitas Informasi, Kualitas Interaksi Layanan, Kepuasan Pengguna, Webqual